Rancang Bangun Aplikasi Absensi Siswa Berbasis Web Menggunakan Metode Waterfall (Studi Kasus: SMK Kesuma Bangsa 2 Depok) - Sri Rama Putri; Iqbal Ardiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
In-depth and detailed information regarding attendance at an activity can determine the productivity or progress of the agency in general. Whereas what we know now in a school there are still many who use conventional attendance records. There are many shortcomings in carrying out attendance by recording conventional attendance, which include the absence of a data storage place so that it takes quite a long time to search for data, not to mention the added number of students in an institution which requires quite a lot of special containers to accommodate information from each number of users. Unfortunately, conventional data collection and attendance systems are impractical in the process of recording attendance to a central server, because it has to be done manually and there is a possibility of errors in the recording process caused by human error, and data loss often occurs because the data is only in the form of sheets. -sheets of paper. Therefore, it is necessary to have a web-based student attendance application system. The method used is the waterfall method because this method allows for departmentalization and control. the process of developing a one by one phase model, thereby minimizing errors that might occur.